Water quality of Ba Lat estuary - Hoa, Bui Thi; Huan, Nguyen Xuan; Nam, Nguyen Thanh; Ha, Le Thu (Vietnam Journal of Marine Science and Technology, 2020)
Ba Lat estuary is the large mouth of the Red river; every year, the Ba Lat estuary receives million cubic meters of water before the water is dissolved in the sea. Therefore, polluted materials in the water from the continent are also transported to the sea through the estuary. However, the volume of the water pouring into the sea varies with the season. In this paper, the water quality at Ba Lat estuary (Red river) was surveyed in July 2017 representing the Southwest wind season (rainy season) and in October 2017 representing the Northeast wind season (dry season). The research results show that the values of chemical parameters of water at Ba Lat estuary changed according to the season: the average temperature of water in the rainy season was 2.5oC higher than in the dry season; average pH in the rainy season (7.45 ± 0.36) was higher than that in the dry season (7.01 ± 0.17). Parameters such as conductivity, salinity, NO3-N, NH3-N, PO4-P, total grease, Fe and Zn in the dry season were 1.22–2.92 times higher than in the rainy season. Concentration of some nutrition (including NO3-N; NH3-N; PO4-P and SiO3-Si), heavy metals (Fe, Zn), and total grease in the water were high, in which NO3-N ranged from 0.565 mg/l to 1.129 mg/l; NH3-N ranged from 0.139 mg/l to 6.16 mg/l, 1.53 to 4.47 times higher than the standard of Vietnam. PO4-P ranged from 0.16 mg/l to 0.82 mg/l, which was 2 to 3.14 times higher than the standard. SiO3-Si ranged from 3.49 mg/l to 5.31 mg/l. Iron concentration in the water was 2.2 to 9.7 times higher than the standard and not different between the two seasons. Zn ranged from 0.64 mg/l to 2.56 mg/l, 1.28 to 5.12 times higher than the standard. Total grease ranged from 2.8 mg/l to 7.0 mg/l, 5.6 to 14 times higher than the standard. Other parameters such as DO, BOD5, Fe, SiO3-Si in the Northeast wind season were 1.01 to 1.35 times lower than in the Southwest wind season. In particular, DO ranged from 3.75 mg/l to 4.99 mg/l, lower than the QCVN 10-MT: 2015 standard and the DO was not suitable for the growth and development of aquatic life. Iron concentration ranged from 2.172 mg/l to 2.209 mg/l, 4.3 to 4.4 times higher than the standard. Water quality also varies with the space, most notably in electrical conductivity, salinity and grease. In particular, the salinity and conductivity tend to increase gradually from the river to the sea, the total oil and grease reached the highest point at BL7 in both phases, and NO3-N in phase 2 reached the highest value at BL6 to BL11.